Faktor Risiko Mortalitas Pasien Sepsis di Instalasi Gawat Darurat: Tinjauan Sistematis - Anugerah Hardianti; Ahsan Ahsan; Heri Kristianto (Direktorat Politeknik Kesehatan Makassar, 2025)
Sepsis is a medical emergency with a high mortality rate worldwide. Identifying risk factors for sepsis is crucial to optimizing outcomes for sepsis patients in the emergency department (ED). This systematic review aims to identify risk factors for mortality in sepsis patients in the ED. Literature search strategies were conducted using the PubMed, ProQuest, and ScienceDirect databases with a combination of keywords including “Risk factor,” “Sepsis,” “Mortality,” and “Emergency Department,” utilizing Boolean operators. This review follows the PRISMA protocol and includes English-language articles published between 2019 and 2024. Inclusion criteria include quantitative research articles (cohort studies, case-control studies, or cross-sectional studies), studies evaluating mortality risk factors in sepsis patients in the ED, and a minimum sample size of 50 patients. Exclusion criteria included qualitative studies, systematic reviews, narrative reviews, meta-analyses, articles without complete data, settings outside the ED, and studies that did not analyze mortality risk factors. Of the 23,917 articles identified, nine met the criteria and were assessed for eligibility using the JBI and analyzed narratively. The review of nine studies (seven cohort studies, one case-control study, and one cross-sectional study) found that most studies indicated that lactate levels ≥2 mmol/L (67%) and SOFA scores ≥2 (56%) were strong predictors of mortality. Other contributing factors included advanced age, gender, and comorbidities. These findings suggest that measuring lactate and SOFA biomarkers during triage in the ED has the potential to improve early detection and prompt intervention, such as fluid resuscitation and antibiotic administration within the golden hour, for high-risk sepsis patients. Keywords: Risk factors; Emergency Department; Mortality; Sepsis